PENGARUH MOTIVASI DAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PEMAHAMAN DAN PELAYANAN SEBAGAI VARIABEL MODERASI - DESYDERIA FIRNANDA, SHINTA (Jurnal Akuntansi AKUNESA, 2017)
This study examines the effects of motivation and tax penalties on taxpayer compliance of self-employed professionals with the addition of understanding and service as a moderation variable. This study uses survey approach with questionnaires as the basis of data retrieval. Based on the test results using SPSS 22, it shows that motivation influencing compliance and service can moderate the relationship between tax penalties to compliance. While tax penalties have no effect on compliance, understanding and service can not moderate the relationship between motivation to compliance, as well as understanding can not moderate the relationship between tax penalties against compliance. This study is based on Crowding Theory and Slippery Slope Framework.